Characterization and In Vivo Validation of a Three-Dimensional Multi-Cellular Culture Model to Study Heterotypic Interactions in Colorectal Cancer Cell Growth, Invasion and Metastasis - Cattin, Sarah; Ramont, Laurent; Rüegg, Curzio (Frontiers in Bioengineering and Biotechnology, 2018)
Colorectal cancer (CRC) is the third cause of cancer-related mortality in industrialized countries. Local invasion and metastasis formation are events associated with poor prognosis for which today there are no effective therapeutic options. Invasion and metastasis are strongly modulated by cells of the tumor microenvironment (TME), in particular fibroblasts and endothelial cells. Unraveling interactions between tumor cells and cells of the TME may identify novel mechanisms and therapeutic targets to prevent or treat metastasis. We report here the development and in vivo validation of a 3D tumor spheroid model to study the interactions between CRC cells, fibroblasts and endothelial cells in vitro. Co-cultured fibroblasts promoted SW620 and HCT116 CRC spheroid invasion, and this was prevented by the SRC and FGFR kinase inhibitors Dasatinib and Erdafitinib, respectively. To validate these findings in vivo, we injected SW620 cells alone or together with fibroblasts orthotopically in the caecum of mice. Co-injection with fibroblasts promoted lung metastasis growth, which was fully reversed by treatment with Dasatinib or Erdafitinib. Co-culture of SW620 or HCT116 CRC spheroids with endothelial cells suppressed spheroid growth while it had no effect on cancer cell migration or invasion. Consistent with this in vitro effect, co-injected endothelial cells significantly inhibited primary tumor growth in vivo. From these experiments we conclude that effects on cancer cell invasion and growth induced by co-cultured TME cells and drug treatment in the 3D spheroid model in vitro, are predictive of in vivo effects. The 3D spheroid model may be considered as an attractive model to study the effect of heterotypic cellular interactions and drug activities on cancer cells, as animal testing alternative. This model may be adapted and further developed to include different types of cancer and host cells and to investigate additional functions and drugs.